External morphology and osteology of Darevskia rudis (Bedriaga, 1886), with a taxonomic revision of the Pontic and Small-Caucasus populations (Squamata: Lacertidae) - Arribas, Oscar; Ilgaz, Çeti̇n; Kumlutaş, Yusuf; Durmuş, Sali̇h Hakan; Avci, Azi̇z; Üzüm, Nazan (Zootaxa, 2013)
A broad sample of Darevskia rudis from the main part of its range was reviewed with regard to external morphology (dis-criminant, UPGMA, MST and ANOVA analyses) and osteology. Darevskia bithynica is raised to species rank, with two subspecies: D. b. bithynica and D. b. tristis. The other subspecies are fairly similar (D. r. rudis being the most different). Two singular populations are described as subspecies: D. r. mirabilis ssp. nov. from Kaçkar Mountains, geographically adjoins the otherwise different D. r. bischoffi and D. r. bolkardaghica ssp. nov., which is geographically isolated but that seems to be very closely related to D. r. obscura.